Self-Monitoring Symptoms in Glaucoma: A Feasibility Study of a Web-Based Diary Tool - Leanne McDonald; Fiona C. Glen; Deanna J. Taylor; David P. Crabb (Journal of Ophthalmology)
Purpose. Glaucoma patients annually spend only a few hours in an eye clinic but spend more than 5000 waking hours engaged in everything else. We propose that patients could self-monitor changes in visual symptoms providing valuable between clinic information; we test the hypothesis that this is feasible using a web-based diary tool. Methods. Ten glaucoma patients with a range of visual field loss took part in an eight-week pilot study. After completing a series of baseline tests, volunteers were prompted to monitor symptoms every three days and complete a diary about their vision during daily life using a bespoke web-based diary tool. Response to an end of a study questionnaire about the usefulness of the exercise was a main outcome measure. Results. Eight of the 10 patients rated the monitoring scheme to be “valuable” or “very valuable.” Completion rate to items was excellent (96%). Themes from a qualitative synthesis of the diary entries related to behavioural aspects of glaucoma. One patient concluded that a constant focus on monitoring symptoms led to negative feelings. Conclusions. A web-based diary tool for monitoring self-reported glaucoma symptoms is practically feasible. The tool must be carefully designed to ensure participants are benefitting, and it is not increasing anxiety.